The Nitrogen Legacy : The Long-Term Effects of Water Pollution on Human Capital - Zaveri, Esha (World Bank, Washington, DC, 2019)
The fallout of nitrogen pollution is considered one of the largest global externalities facing the world, impacting air, water soil and human health. This paper presents new evidence that nitrogen pollution in water is an important determinant of variations in human capital. Data from the Demographic and Health Survey dataset across India, Vietnam, and 33 African countries are combined to analyze the causal links between pollution exposure experienced during the very earliest stages of life and later-life health. Results show that pollution exposure experienced in the critical years of development from the period of birth up until year three – is associated with decreased height as an adult, a well-known indicator of overall health and productivity, and is robust to several statistical checks. Because adult height is related to education, labor productivity, and income, this also implies a loss of earning potential. Results are consistent and show that early-life exposure to nitrogen pollution in water can lower height-for-age scores during childhood in Vietnam and during infancy in Africa. These findings add to the evidence on the enduring consequences of water pollution and identify a critical area for policy intervention.